Metoclopramide-induced rapid-onset psychosis in a child with methylphenidate use: a case report - Gökçen İlçioğlu Ekici; Gülser Şenses Dinç; Ayşegül Neşe Çıtak Kurt (The Turkish Journal of Pediatrics)
Background. Metoclopramide, a dopamine antagonist employed for its antiemetic effects, can precipitate neuropsychiatric adverse effects, including extrapyramidal symptoms and, in a few instances, acute psychosis. Although there have been reports of metoclopramide-induced psychosis in elderly individuals, there is no documentation of such incidents in children as far as we are aware.